2022
DOI: 10.1038/s41467-022-29557-1
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic atroposelective construction of axially chiral N, N- and N, S-1,2-azoles through novel ring formation approach

Abstract: Abstract1,2-Azoles are privileged structures in ligand/catalyst design and widely exist in many important natural products and drugs. In this report, two types of axially chiral 1,2-azoles (naphthyl-isothiazole S-oxides with a stereogenic sulfur center and atropoisomeric naphthyl pyrazoles) are synthesized via modified vinylidene ortho-quinone methide intermediates. Diverse products are acquired in satisfying yields and good to excellent enantioselectivities. The vinylidene ortho-quinone methide intermediates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 70 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…Atroposelective construction of heterobiaryls via VQM intermediates. [40][41][42] Chemistry-A European Journal limits repulsive interactions. These interesting works show that different kinds of catalysts could provide complementarity to accelerate the extensive exploration of chirality compounds.…”
Section: Intramolecular Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Atroposelective construction of heterobiaryls via VQM intermediates. [40][41][42] Chemistry-A European Journal limits repulsive interactions. These interesting works show that different kinds of catalysts could provide complementarity to accelerate the extensive exploration of chirality compounds.…”
Section: Intramolecular Cyclizationmentioning
confidence: 99%
“…In the reaction process, the VQM intermediate Int ‐ 35 was involved and played a key role in stereoselectivity (Scheme 22a) [40] . In 2021, through modified VQM intermediates, they also achieved the synthesis of axially chiral heterobiaryls 66 (bearing both C−C and C−N axes) [41] and two types of axially chiral 1,2‐azoles 68 and 69 , [42] respectively (Scheme 22b and c). Control experiments show that the C−N axis of (1 R , 2 S )‐ 66 and (1 R , 2 R )‐ 66 was more thermodynamically stable than the C−C axis, which could be converted when heated at 110 °C in toluene for 24 h (Scheme 22b).…”
Section: Asymmetric Cyclization Synthesis Of Heterobiarylsmentioning
confidence: 99%
“…Diverse atropisomeric heterobiaryl molecules including axially chiral N , N - and N , S - 1,2-azole scaffolds were synthesized utilizing modified vinylidene orth o -quinone methide precursors 111 and 113 via a ring formation method catalyzed by cinchona alkaloids-derived squalamine L29 and L30 ( Scheme 33 ) [ 98 ]. This work, developed by Yan’s group, simultaneously controlled the atroposelective installation of a stereogenic axis and the formation of a heterocyclic ring.…”
Section: Synthesis Of Axially Chiral Heterobiaryl Scaffold Catalyzed ...mentioning
confidence: 99%
“…Furthermore, the results of the evaluation in vitro showed that the atropisomeric pyrazole products also exhibited promising antiproliferation activity (Scheme 24). [38] Scheme 21. Organocatalytic asymmetric construction of tetrasubstituted carbon stereocenters bearing multiple heteroatoms.…”
Section: Cinchona Alkaloid-based Catalystsmentioning
confidence: 99%